Tbx1 is required for second heart field proliferation in zebrafish - Nevis, Kathleen (2013)
BACKGROUND: The mammalian outflow tract (OFT) and primitive right ventricle arise by accretion of newly differentiated cells to the arterial pole of the heart tube from multi-potent progenitor cells of the second heart field (SHF). While mounting evidence suggests that the genetic pathways regulating SHF development are highly conserved in zebrafish, this topic remains an active area of investigation. RESULTS: Here, we extend previous observations demonstrating that zebrafish tbx1 (van gogh, vgo) mutants show conotruncal defects consistent with a conserved role in SHF-mediated cardiogenesis. Surprisingly, we reveal through double in situ analyses that tbx1 transcripts are excluded from cardiac progenitor cells or differentiated cardiomyocytes, suggesting a non-autonomous role in SHF development. Further, we find that the diminuitive ventricle in vgo animals results from a 25% decrease in cardiomyocyte numbers that occurs subseqent to heart tube stages. Lastly, we report that although SHF progenitors are specified in the absence of Tbx1, they fail to be maintained due to compromised SHF progenitor cell proliferation. CONCLUSION: These studies highlight conservation of the Tbx1 program in zebrafish SHF biology.